Relationship between parenting stress profiles, work-family conflict, and adolescent problem behavior: Variable-centered and person-centered approaches - Ying Yang (PLoS ONE, 2026)
Background Adolescent problem behaviors, including both internalizing (e.g., emotional symptoms) and externalizing difficulties (e.g., conduct problems, hyperactivity), are a significant risk factor in adolescent development. This study assessed the impact of maternal parenting stress on adolescent problem behaviors and explored mechanisms underlying this relationship. Objective This study aimed to (1) identify potential profiles of maternal parenting stress, (2) examine differences in adolescent problem behaviors across these profiles, and (3) determine whether maternal work-family conflict mediates the relationship between maternal stress profiles and adolescent problem behaviors. Methods In this cross-sectional study, data were collected from 846 mother-child subject pairs through self-report instruments completed by both mothers and adolescents. Standardized measures were used to assess parenting stress, work-family conflict, and problem behavior. The data were subsequently analyzed using latent profile analysis and mediation analysis. Result (1) Four maternal stress profiles were identified: low-stress, middle-stress-low interaction disorder, middle-stress, and high-stress profiles. (2) Significant differences in adolescent problem behaviors were observed across these profiles. (3) The other three profiles significantly predicted adolescent problem behaviors compared to the low-stress group. (4) Using the low-stress type as the reference, maternal work interference with family significantly mediated the relationship between the remaining three stress profiles and adolescent problem behaviors.